Polycytidylation of mitochondrial mRNAs in Chlamydomonas reinhardtii. Issue 22 (9th October 2017) - Salinas-Giegé, Thalia; Cavaiuolo, Marina; Cognat, Valérie; Ubrig, Elodie; Remacle, Claire; Duchêne, Anne-Marie; Vallon, Olivier; Maréchal-Drouard, Laurence
Abstract: The unicellular photosynthetic organism, Chlamydomonas reinhardtii, represents a powerful model to study mitochondrial gene expression. Here, we show that the 5′- and 3′-extremities of the eight Chlamydomonas mitochondrial mRNAs present two unusual characteristics. First, all mRNAs start primarily at the AUG initiation codon of the coding sequence which is often marked by a cluster of small RNAs. Second, unusual tails are added post-transcriptionally at the 3′-extremity of all mRNAs. The nucleotide composition of the tails is distinct from that described in any other systems and can be partitioned between A/U-rich tails, predominantly composed of Adenosine and Uridine, and C-rich tails composed mostly of Cytidine. Based on 3′ RACE experiments, 22% of mRNAs present C-rich tails, some of them composed of up to 20 consecutive Cs. Polycytidylation is specific to mitochondria and occurs primarily on mRNAs. This unprecedented post-transcriptional modification seems to be a specific feature of the Chlorophyceae class of green algae and points out the existence of novel strategies in mitochondrial gene expression.